Perbedaan Pengaruh Aerobic Low Impact Exercise dan Gaze Stability Exercise terhadap Keseimbangan Dinamis - Apriyani, Ishela; Norlinta, Siti Nadhir Ollin; Jannah, Suci Muqodimmatul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the differences in the effects of the two exercises on the dynamic balance of the elderly. The research method uses a 2-group quasi-experimental design with a